2015
DOI: 10.1002/ccr3.57
|View full text |Cite
|
Sign up to set email alerts
|

Necrobiosis lipoidica associated with Hashimoto's thyroiditis and positive detection of ANA and ASMA autoantibodies

Abstract: Key Clinical MessageNecrobiosis lipoidica (NL) is a rare idiopathic cutaneous condition exceptionally associated with autoimmune thyroiditis. We describe the first case of NL, Hashimoto’s thyroiditis and positive detection of autoantibodies. Appropriate screening for NL in patients with autoimmune thyroiditis may clarify its real incidence and the existence of a common pathogenetic pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 5 publications
0
7
0
1
Order By: Relevance
“…Increasing evidence suggests that NL may be induced by immunological mechanisms, in which either an immune complex disease or autoantibodies targeting vessel wall tissue antigens represent the triggering events. This hypothesis is supported by the detection of immunoglobulins and complement factor deposits, especially immunoglobulin M (IgM), C3, and fibrin, in vessel walls and the dermal-epidermal junction of the affected skin [6,17]. An immune-mediated process is also suggested by the stronger association with type 1 DM rather than with type 2 DM.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Increasing evidence suggests that NL may be induced by immunological mechanisms, in which either an immune complex disease or autoantibodies targeting vessel wall tissue antigens represent the triggering events. This hypothesis is supported by the detection of immunoglobulins and complement factor deposits, especially immunoglobulin M (IgM), C3, and fibrin, in vessel walls and the dermal-epidermal junction of the affected skin [6,17]. An immune-mediated process is also suggested by the stronger association with type 1 DM rather than with type 2 DM.…”
Section: Introductionmentioning
confidence: 94%
“…The paucity of epidemiological data on NL in other immune-mediated conditions could partly be explained by the absence of adequate clinical screening for this disease, which has traditionally been considered a specific manifestation of DM. Furthermore, most of the cohort studies documented in the literature have focused on therapeutic rather than epidemiological aspects [6]. In this regard, a recent multicenter retrospective study, examining the data of 52 patients with NL of the lower legs, found a prevalence of thyroid function disorders in 13%, compared to 5.5% in the general population, suggesting that NL could be associated with other conditions than DM alone [7].…”
Section: Introductionmentioning
confidence: 99%
“…Thyroid disorders, such as Graves disease and Hashimoto disease, have been documented in certain patients with NL lesions on the lower extremities [10,29,100]. Erfurt-Berge et al reported in their 2012 study, that from a group of 52 participants, 7 individuals were found to have thyroid disease [63].…”
Section: Thyroid Diseasementioning
confidence: 99%
“…Erfurt-Berge et al reported in their 2012 study, that from a group of 52 participants, 7 individuals were found to have thyroid disease [63]. There is currently no established causal association between the two disorders; nonetheless, there has been speculation regarding the presence of autoantibodies or deposition of autoimmune complexes [29,100]. In both cases, there is growing evidence suggesting that NL may be triggered by an immunological mechanism, in which either an immune complex disease or autoantibodies are directed against vessel wall tissue antigens [100].…”
Section: Thyroid Diseasementioning
confidence: 99%
“…zu Diabetes-Patienten ohne NL [16]. Insbesondere ein assoziiertes Auftreten einer Autoimmunthyreoiditis sollte abgeklärt werden [19]. Eigene Untersuchungen zeigen, dass das Auftreten von Bluthochdruck, Übergewicht und Schilddrüsenfunktionsstörungen mit dem Auftreten von ulzerierten NL-Läsionen einherzugehen scheint [12].…”
Section: Assoziierte Erkrankungenunclassified